PHYSICAL THERAPY OF VERTEBROGENIC CERVICOCRANIALGIA - Badyin, I. Yu.; Gorsha, O. V.; Gorsha, V. I. (Rehabilitation and Recreation, 2024)
The aim of the study was to investigate the effects of kinesiotaping, PRP- therapy (platelet-rich plasma injection) and therapeutic gymnastics on the clinical condition and quality of life (QOL) of young people with vertebrogenic cervicocranialgia syndrome (VCS). The clinical efficacy of these methods of physical therapy (PT) was evaluated in patients of the main group (MG) – 38 young people with VCS. The control group (CG) included 30 patients with VCS of the appropriate age and sex who had drug therapy (NSAIDs and muscle relaxants). Computed tomography and X-ray of cervical spine with functional tests were performed in addition to the routine examination. A questionnaire was administered using Oswestry disability index (a scale for assessing the degree of disability caused by spinal pathology) and the MOS-SF-36 questionnaire. Pain intensity was assessed by the VAS scale. In the control group, after 5–7 days of observation (after PRP-therapy), a 9.2 mm reduction in pain was found. In the main group, the pain gradation decreased by 5.72 mm, and exceeded the degree of pain in the group with anti-inflammatory drugs (p>0.05). A month later, in the MG, after the addition of kinesiotaping and therapeutic gymnastics, pain decreased by 32.9 mm (p<0.05), and in the CG, while taking medications, a significant pain reduction by 21.5 mm was noted compared to the initial pain (p<0.05). But the clinical effectiveness of drug therapy was less pronounced. After 3 months, a statistically significant improvement of PT methods effectiveness was found (difference of 11.7 mm (p<0.05) between MG and CG). So, the study found that the applied PT methods can stably reduce the manifestation of pain VCS. The use of PT can improve QOL in patients with VCS by reducing pain, restoring spinal mobility, expanding the movement regimen and active lifestyle. The combined use of kinesiotaping, PRP-therapy and therapeutic gymnastics is relevant in optimising the treatment of cervical osteochondrosis manifestations and dysplastic instability of spine. This can increase the effectiveness and safety of treatment and can be recommended for widespread usage.